CTNI-46. PHASE I OPEN-LABEL, SINGLE-CENTER, DOSE ESCALATION STUDY (NCT02423525) OF PULSATILE AFATINIB IN PATIENTS WITH BRAIN CANCER. (12th November 2021) - Wagle, Naveed; Juarez, Tiffany; Carrillo, Jose; Heng, Annie; Gill, Jaya; Nguyen, Minhdan; Truong, Judy; Boucher, Najee; Archer, Ashley; Nguyen, Hanh; Nomura, Natsuko; Yenugonda, Venkata; et al.
Abstract: Afatinib is a small molecule, selective and irreversible ErbB family blocker. In preclinical models it effectively inhibits EGFR, HER2 and HER4 phosphorylation resulting in tumor growth inhibition and is approved for the treatment of EGFR-mutated metastatic non-small cell lung carcinoma and metastatic squamous cell lung carcinoma. Pulse dosing afatinib could potentially increase CNS exposure to reach therapeutic levels while allowing a recovery period to mitigate toxicities. We are reporting the results of a Phase I open-label, single-center, '3 + 3' dose escalation study to determine the safety and tolerability of pulsatile Afatinib in patients with brain cancer and to define a recommended phase 2 dose. The study assessed the exposure of Afatinib in cerebrospinal fluid and serum, objective tumor response according to RANO criteria, progression-free survival, and overall survival, and will explore the association between molecular phenotypes and patient response. In total, 26 patients were screened and 24 were enrolled (median age 60, 78% male, 87.5% Caucasian, glioblastoma N=16, chordoma N=3, brain metastases N=2, meningioma N=1, anaplastic mixed oligoastrocytoma N=1). Patients had received a median of 2.5 prior treatments. The study proceeded through the 4 dosing cohorts without reaching dose-limiting toxicity: Cohort 1 (80mg every 4 days) N=3; Cohort 2 (120mg every 4 days) N=3; Cohort 3 (180mg every 4 days) N=7, including replacement patients; Cohort 4 (280mg every 7 days) N=11. Diarrhea (75%), rash (75%), nausea/vomiting (37.5%), fatigue (29.2%), anorexia (25%), and limb edema (16.7%) were the most common side effects. There were no CTCAE defined grade 4 toxicities. Grade 3 side effects infrequently occurred in the highest dosing cohort and once in each cohort 2 and 3. These results demonstrate that pulsatile Afatinib at a dose of 280mg every 7 days is safe and tolerable for patients with brain involving cancers.